Zingiber officinale and oxidative stress in patients with ulcerative colitis: A randomized, placebo-controlled, clinical trial. (April 2019) - Nikkhah-Bodaghi, Mehrnaz; Maleki, Iradj; Agah, Shahram; Hekmatdoost, Azita
Highlights: Ginger can reduce disease activity in Ulcerative Colitis. Ginger can increase quality of life in patients with Ulcerative Colitis. Ginger may reduce oxidative stress in Ulcerative Colitis. Abstract: Objectives: Oxidative stress plays an essential role in ulcerative colitis (UC) initiation and severity. We aimed to investigate the effect of ginger as a well-known antioxidant agent on the quality of life, disease activity index and oxidative stress in patients with UC. Methods: Forty six patients with active mild to moderate UC randomly assigned to consume 2000 mg/day dried ginger powder in 4 capsules or similar placebo capsules for 12 weeks. Disease activity index, quality of life and some oxidative stress factors were measured before, at the middle and at the end of the intervention through valid and reliable questionnaires and blood sampling. Results: Ginger reduced Malondialdehyde (MDA) significantly after 6 weeks (p = 0.003) and 12 weeks (p < 0.001) of intervention, whereas it did not affect serum total anti-oxidant capacity (TAC). The scores of severity of disease activity at 12th week was significantly improved in ginger group in comparison to placebo (p = 0.017). Moreover, ginger increased patients quality of life significantly at 12 th week (p = 0.039). Conclusion: Our data indicate that ginger supplementation can improve treatment of patients with UC. Further clinical trials with different dosages and duration of ginger or its standard extract supplementation are needed to obtain firm conclusion.